The Physiopsychological Impact of Smartphone Use on Cognitive Load, Emotional Regulation, and Brain Connectivity: An EEG Study - Hu, Yue (International Journal of Public Health and Medical Research, 2025)
This study utilizes electroencephalography (EEG) to examine the neurocognitive effects of typical smartphone activities—video watching, social interaction, and gaming—on brainwave activity, cognitive load, and emotional engagement. Findings reveal: High cognitive-load tasks (e.g., strategy games) significantly increase β and γ wave activity and delay post-task neural recovery. Social tasks elevate θ wave activity, indicating heightened emotional involvement. Video watching induces α wave enhancement, reflecting a more relaxed mental state. Significant differences in EEG frequency bands were observed across task types, though no strong correlation was found with Internet Addiction Test (IAT) scores. The results offer valuable insights for sectors such as education, corporate focus management, digital health development, and user interface optimization. Further research is recommended using multimodal physiological data and extended observation periods.